Psychological Research in Fibromyalgia: The Search for Explanatory Phenomena - Michael D Boissevan (Pain Research and Management)
This article reviews four areas of psychological research in fibromyalgia. First, the literature on depression in fibromyalgia shows that although the preponderance of studies demonstrate that fibromyalgia patients are more depressed than comparable medical patients, rigorous disconfirming evidence exists. Thus the role of depression in fibromyalgia remains unclear because consistent levels of depression are not found either between samples or between subjects. Second, the role of pain perception in fibromyalgia shows that fibromyalgia patients are consistently more responsive to aversive stimulation than other subjects with chronic pain. This pattern of hyper-responsiveness appears to be generalized, rather than localized to tender points. These results are discussed in terms of potential central nervous system mechanisms. Third, original research in clinical cognitive psychology is presented that shows that fibromyalgia patients do not appear to demonstrate cognitive biases which are distinct from myofascial pain. Although extremely preliminary, these results argue against a unique psychological explanation for fibromyalgia symptoms. Fourth, neuropsychological research demonstrates a pattern of generalized inhibition of information processing that emulates that observed in depressive illness, except that fibromyalgia patients tend not to show the compromise in right hemisphere processing seen in depression. This suggests that cognitive abnormalities in fibromyalgia may be distinct from those seen in depression. The psychological research reviewed suggests that central nervous system anomalies may be implicated in the syndrome of fibromyalgia, but the evidence for motivated or affective psychological involvement in the syndrome remains equivocal. Suggestions are provided for future research.